INDEKS MASSA TUBUH (IMT) TERHADAP SIKLUS HAID WANITA USIA SUBUR - Syari, Mila; Sari Sinaga, Elvina; Ramini Harahap, Novy; Nasuition, Pratiwi (AHM Center, 2023)
Menstruation is bleeding with a certain period which is part of a woman's biological function throughout her life cycle. BMI is a tool to measure a person's nutritional status which is interpreted in 3 criteria, namely thin, normal and fat. Based on Indonesia's 2018 Riskesdas regarding nutritional status according to BMI population aged > 18 years showed that 8.7% experienced malnutrition, 13.5% experienced excess nutrition, and 15.4% experienced obesity. The purpose of this study was to determine the relationship between BMI and the menstrual cycle in women of childbearing age at the Panji Husada Clinic. Analytical quantitative research method with cross sectional design. The number of samples is 49 people. The sampling technique is simple random sampling. The data collection technique used by researchers is a correlational descriptive approach. The data collection tool is using a checklist sheet. Data analysis test was carried out univariate and bivariate (chi-square test). The results of the research from the chi-square obtained p = 0.516, meaning that there is a not relationship between BMI and the menstrual cycle of women of childbearing age at the Panji Husada Clinic, Kabun District. Suggestions for the Midwifery SI Study Program This research can be an additional reference regarding the relationship between BMI and the menstrual cycle of women of childbearing age.